A New Form of Evidence to Date the Madaba Map Mosaic - Madden, Andrew M. (Liber Annuus, 2012)
Abstract One lingering problem facing researchers of the Madaba Map mosaic is its precise date of manufacture. The historical geography evident in the mosaic and stylistic considerations are generally viewed as the essential dating indicators. Michele Piccirillo suggested that the Map and mosaics from the nearby church of Sts. Lot and Procopius were paved by the same workshop, primarily on the strength of style. An analysis of the technique employed by the artisans to illustrate certain detailing elements common to these mosaics leads to the compelling belief that they were indeed manufactured by the same workshop. The pavement from Sts. Lot and Procopius can be reliably dated by its dedicatory inscription to a specific year that also accords with the period ascertained by the Map’s historical evidence. Consequently, this should stand as the probable date for the creation of the Map mosaic.